Synthesis, Characterization and Catalytic Activity of Nano-Iron (II) Schiff Base Complex in Suzuki-Miyaura Cross Coupling Reaction - M. Ansari, Rasheeda; Ramachandra Bat, Badekai (International Journal of Engineering and Technology, 2018)
A new nano-iron (II) Schiff base complex, [Fe(L)] where L is 1-((pyridin-2-ylimino)methyl)naphthalen-2-ol with octahedral geometry has been synthesized by the sonochemical (Ultrasonic irradiation) method. This method can promote the formation of nano-sized particles in short time with improved yield toward conventional method. The complex was characterized by FTIR, UV-Vis, TGA, SEM and elemental analysis. Particle size of synthesized complex was calculated from particle size analysis. Catalytic activity of the prepared complex was studied for Suzuki-Miyaura cross-coupling reaction. The synthesized complex showed great potential in catalytic activity with less concentration.Â
Keywords: Biphenyl; Iron Catalyst; Nano Complex; Schiff base; Suzuki-Miyaura coupling.